Teacher Empowerment Management in Islamic Boarding Schools Jambi Province - Nur Komariah; Ruhiat Ruhiat; Nanda Saputra; Muhammad Abu Bakar (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
Teacher empowerment is an effort of the leadership of educational institutions to improve teacher professionalism in teaching. This study aims to analyze teacher empowerment planning, teacher empowerment implementation, and teacher empowerment evaluation. Using a descriptive qualitative approach with observation data collection techniques, interviews, and documentation. Data analysis used Miles and Huberman's model and analyzed data using data triangulation.  The results of this study are: in planning activities, boarding school leaders plan facilities and infrastructure, educators, provide autonomy and develop teacher competence. In implementing activities, the boarding school leadership instructs the preparation of learning programs, gives confidence in managing classes, utilizes facilities and infrastructure, optimizes teachers as mentors, class administration, and teacher leadership, and optimizes teachers to develop learning evaluations. Evaluation, Checking curriculum documents, supervising classrooms, and providing supervision. The leadership of the boarding school has tried to improve the empowerment of teachers to build student entrepreneurship but teacher empowerment has not been fully achieved, as teachers have not fully met the qualifications as professional educators, and the impact of the development of student entrepreneurship has not been optimal.